Hubungan Penerapan Perilaku KADARZI dengan Status Gizi Balita di Puskesmas Mengwi I Kabupaten Badung - Anak Agung Istri Ardhia Pramesti Kiyanti; Anny Eka Pratiwi; Dewa Ayu Putu Ratna Juwita (Fakultas Ilmu Kedokteran dan Ilmu Kesehatan, Universitas Warmadewa, 2023)
Lately, undernourished children coexist with toddlers with toddlers who are overnourished. To overcome these obstacles, the government has made various efforts to improve the nutritional status of Indonesian children. One of them is through the KADARZI (Keluarga Sadar Gizi) programme, which is defined as a family's awareness to detect, anticipate, and resolve any nutritional issues in each of its members. This research objective is to examine the association between the application of KADARZI behavior and the nutritional status of young children, using cross-sectional analytical approach. The participants in this research consist of 100 mothers and toddlers who are in the age range of 6 to 59 months, and live in the operational area of Puskesmas Mengwi I Badung. The respondent selection is done by using a consecutive sampling technique. After the data collection procedure was completed, each variable will be processed by using univariate and bivariate methods. Findings from this study reveal that the majority of toddlers are male (59%) in the age range of 36 to 47 months (35%), and do not experience any nutritional issues according to the TB/U and BB/U index (100% and 69%), also BB/TB index (88%). In addition, 54 out of 100 families did not implement the KADARZI behavior comprehensively. According to the result of chi-square analysis, p-value obtained is 0.005 (p â‰¤ 0.05). It indicates a significant correlation between the application of KADARZI behavior and the nutritional status of toddlers in the operational area of Puskesmas Mengwi I Badung. The value of prevalence ratio (PR) obtained is 9.370 with a 95% confidence interval between range 1.257 to 69.863. After this research is done, it is recommended to enhance collaboration between POKJA (Kelompok Kerja) IV and government institutions to raise public awareness regarding the implementation of KADARZI behavior.